Computerisation of the Singapore courts and its impact on the legal profession - Ranganathan Kalpana (2011)
The Singapore Judicial system is becoming computer-savvy. As the Information and Computer Age gains momentum, it is inevitable that every aspect of life will be affected. The Government's push to make Singapore the Information Technology Center for the region and to place Singapore on the global Information Technology map has meant that every aspect of the administration is not spared. The Judiciary in the past 11 years has made tremendous improvements in this direction, to make it relevant in the 21st century. The push is towards paperless court hearings and trials.